The role of positive emotional culture as a mediator between symmetrical internal communication and organizational identification: Procedural justice climate as a moderator - Mulyana, Rissa Septiani; Salendu, Alice (Jurnal Psikologi Terapan dan Pendidikan, 2025)
Organizational identification is crucial for understanding how employees internalize their company’s values, goals, and identity. Understanding the dynamics of organizational identification can help companies foster a more harmonious and productive work environment and develop effective management strategies to retain and enhance employee engagement. This research aims to elucidate the role of a positive emotional culture in the relationship between symmetrical internal communication and organizational identification, moderated by procedural justice climate. 158 participants from various industries in Indonesia were involved in this study, selected through convenience sampling. Data collection was conducted via an online survey using Google Forms. Data analysis employed Model 4 and Model 14 of Hayes’ PROCESS, utilizing SPSS version 29.0.1.0. The results indicate that a positive emotional culture significantly mediates the relationship between symmetrical internal communication and organizational identification. However, there is no moderating effect of the procedural justice climate in this relationship. This research is valuable for organizational management, as it highlights the importance of fostering symmetrical internal communication to cultivate a positive emotional culture, which, in turn, can enhance employee organizational identification.